The Risks and Benefits of Skiing on Pregnancy - Szplit, Ewa; Wolski, Adam; Michnowska, Wiktoria; Pustuła, Paweł; Bilyk, Andrii; Hebda, Patryk; Król, Maria; Patalong, Mikołaj; Więckowska, Katarzyna; Bruska, Natalia (Quality in Sport, 2026)
Background: Participating in skiing during pregnancy raises clinical concerns about maternal and fetal safety due to the physiological demands of endurance activity, environmental exposure, and potential injury risk. While regular physical activity is widely acknowledged to have maternal and fetal health advantages, evidence specific to downhill and cross-country skiing across studies is limited. Aim: This research paper aims to review the latest literature on the risks and benefits of skiing on pregnancy. Particular attention was paid to endurance training, injuries, cardiovascular adaptations, hypoglycemia, altitude exposure, thermoregulation, and psychological well-being. Material and methods: The study analyzed published articles on the possible risks and benefits of skiing during pregnancy. The source material was collected from PubMed, Scopus, and Google Scholar using keywords related to skiing and pregnancy. Various guidelines were also analyzed. Results: Skiing during pregnancy may reduce the risk of gestational diabetes, improve maternal glucose regulation and cardiovascular health, support favorable obstetric outcomes, alleviate low back pain, promote beneficial infant cardiovascular adaptations, and enhance psychological well-being. However, skiing carries risks related to falls and collisions, particularly with high-intensity activity and postpartum. Additional caution is advised regarding cardiovascular strain, hypoglycemia, and high-altitude exposure, especially for pregnant women with pre-existing medical or obstetric conditions. Conclusions: There is limited data focused specifically on skiing during pregnancy. As a result, recommendations on whether it is safe or not to ski in pregnancy are inconclusive. Further research on the topic is required to develop knowledgeable and clear guidelines for pregnant skiers, specifically separating results on recreational and athletic pregnant skiers and differentiating between skiing disciplines.